Effects of a virtual English club on modern languages students from ECCI (2014)
Nowadays it is important to learn a second language, in particular English because it has become a global language. English is the leading language in international communication because of the growing necessity that nations have to develop all kind of international trade agreements and also the need that people have when using internet, which has become a useful tool for carrying out daily activities. Through this situation, English has become a language that is used in the entire world in comparison to other languages that are just spoken in some areas. As stated by Teachers of English to Speakers of other Languages